SOME PSYCHOLOGICAL CONSIDERATIONS IN THE OBJECTIVES AND DESIGN OF AN ELEMENTARY-SCHOOL SCIENCE PROGRAM. - Ausubel, David P. (Science Education, 1963)
The article examines some psychological considerations in the objectives and design of an elementary school science program in the United States. Evidently, the elementary school child is completely dependent upon current or recently prior concrete-empirical experience for the meaningful understanding or manipulation of relational propostitions. Teachers therefore cannot hope to reduce science to first principles and basic abstract laws, and must then influence students to study science in the order of their phenomenological complexity.